The role of credit rationing and collateral in debt financing - Eike Houben; Peter Nippel (Universität Kiel, Institut für Betriebswirtschaftslehre, 2001)
Credit rationing and the use of collateral are widely observed in debt financing. To our view there is yet no appropriate theoretical explanation for these facts. In the standard debt financing models the occurrence of credit rationing can be explained based on suitable assumptions. But those are by no means general. Furthermore, the use and the form of collateral is limited. In our model we show that credit rationing and the use of collateral are always necessary for debt financing if lenders are rational. We do so under less strict assumptions which are, to our understanding, much more realistic than those typical for standard adverse selection or moral hazard models. We assume that the borrower's opportunity set is "unbounded", at least from the viewpoint of the lender. This means that no arbitrary restrictions are imposed on the set of possible distributions of future cash flow from which the borrower can unobservably choose one. As a result a rational lender granting a pure debt should never take any risk, neither an exogenous one resulting from the project nor a an endogenous one resulting from the information asymmetry. Furthermore, we extend the set of possible collateral to property rights over physical and non physical assets, and explain how a superior lender's information can work as collateral.
Keywords: D23; D82; G20; 650; credit rationing; debt; asymmetric information; collateral